Assessment of The Application of Social Media Among Muslims in Tertiary Institutions and Its Implications on Their Lives in Kaduna State, Nigeria - Ahmad Abubakar; Shafa’at Ahmad Aliyu (Bulletin of Islamic Research, 2024)
The assessment of the application of social media among Muslims in tertiary institutions and its implications on their lives in Kaduna State was embarked as result of observed influence of social media on various spheres of lives. Insulting, scoffing shamelessly divulge of sexual activities, spread of pornography and false information are rampant on social media. Thus, the research aimed to examine how social media is being misused, evaluate the factors that lead to its misuse and assess its impacts. The literature review was based on the variables in the research topic and other related variables. Survey method was adopted and the population was studied by sampling four tertiary institutions from the three senatorial zones of Kaduna State, where 450 questionnaires were distributed to academic staff and undergraduate students of Islamic Studies Departments of the selected educational institutions. The research revealed that, utilization of various social media among Muslims in tertiary institutions of Kaduna State is relatively high and users rarely strictly adhere to Islamic ethics of using social media. Youths are the most common group that misuse social media, by posting, sharing or liking false news/rumors, misinformation or distorting facts about Islam, widening of disunity among Muslims, promoting indecency and immorality, uttering hate speech and exchanging bitter words. Poor parental training and control, failure to engage oneself with useful and beneficial activities, lack of awareness on proper utilization of social media, redundancy and addiction are the factors that lead to misuse of social media. The positive impact of the usage of social media includes dissemination of the teachings of Islam, improving relating and interacting between families, colleagues and friends, and creating easy access to knowledge and awareness. The negative impact includes inculcating laziness and decreasing performance, distorting Islamic teachings and spreading false new, increase in displaying nudity, illegal relationship, immorality, and increases in the rate of gambling and idleness. The study recommends that Hisbah should collaborate with Muslim preachers to check mate social media activities among Muslims.